Robust Multi-Dimensional Trust Computing Mechanism for Cloud Computing (Jurnal Teknologi (Sciences & Engineering), 2014)
Cloud computing has become the most promising way of purchasing computing resources over the Internet. The main advantage of .cloud computing is its economic advantages over the traditional computing resource provisioning. For cloud computing to become acceptable to wider audience, it is necessary to maintain the quality of service (QoS) commitments specified in the service level agreement. In this paper, the authors propose a robust multi-level trust computing mechanism that can be used to track the performance of cloud systems using multiple QoS attributes. In addition, tests carried out show that the proposed mechanism is more robust than the ones published in the literature.